2020
DOI: 10.1108/jsbed-04-2020-0133
|View full text |Cite
|
Sign up to set email alerts
|

Trade credit and firm profitability: moderation analysis of intercompany financing in Italy

Abstract: PurposeThe purpose of this paper is to verify whether the benefits gained by granting extended payment terms can lead to higher profitability for Italian companies. Moreover, the analysis aims to investigate whether trade credit offered at a higher level than the sector average can contribute to the profitability of companies. Finally, it aims to test whether the profitability connected to granting trade credit is higher for the unconstrained and financially sound companies.Design/methodology/approachThe empir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
(91 reference statements)
0
3
1
Order By: Relevance
“…However, an important detail that has not been addressed in this literature is the dependency of certain firms on TC as a source of financing, which can significantly influence their financing policies. Furthermore, our findings do not completely support the conclusions drawn in previous studies (e.g., Aktas et al, 2012;Goto et al, 2015;Dary and James, 2019;Bussoli and Jonte, 2020). The common conclusion offered in these studies is that TC is positively associated with performance measures.…”
Section: Introductioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, an important detail that has not been addressed in this literature is the dependency of certain firms on TC as a source of financing, which can significantly influence their financing policies. Furthermore, our findings do not completely support the conclusions drawn in previous studies (e.g., Aktas et al, 2012;Goto et al, 2015;Dary and James, 2019;Bussoli and Jonte, 2020). The common conclusion offered in these studies is that TC is positively associated with performance measures.…”
Section: Introductioncontrasting
confidence: 99%
“…This study makes the following contributions to the literature on trade credit. The majority of previous research has been conducted in Western countries (Dary and James, 2019;Bussoli and Jonte, 2020) or large Asian countries such as China and Korea (Hyun, 2017;Yano and Shiraishi, 2020). However, there has been a lack of investigation into the consequences of borrowing for financial reasons in the wider Asian context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Linking trade credit with a firm's financial performance, a recent study conducted by Bussol and Conte (2020) reported a negative influence of aggressive trade credit policies on corporate financial efficiency. Offering trade credit, specifically, during financial distress could hamper the financial performance through creating the liquidity problem.…”
Section: Review Of Literaturementioning
confidence: 99%